2005
DOI: 10.1192/bjp.186.6.480
|View full text |Cite
|
Sign up to set email alerts
|

‘Goodbye and good luck’: the mental health needs and treatment experiences of British ex-service personnel

Abstract: Depression is more common than post-traumatic stress disorder in UK ex-service personnel. Only about half of those who have a diagnosis are seeking help currently, and few see specialists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
106
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 128 publications
(113 citation statements)
references
References 22 publications
4
106
0
3
Order By: Relevance
“…A small cross-sectional study in the UK of Gulf, Bosnia and 'Era' (personnel who served in the military at the same time but were not deployed on these operations) veterans who had all left the military revealed the same findings (Iversen 2005b). This is mirrored in both the stillserving US military population (Riddle 2007) and in the UK general population (Jenkins 1997).…”
Section: Common Mental Health Problems In Veteransmentioning
confidence: 63%
See 2 more Smart Citations
“…A small cross-sectional study in the UK of Gulf, Bosnia and 'Era' (personnel who served in the military at the same time but were not deployed on these operations) veterans who had all left the military revealed the same findings (Iversen 2005b). This is mirrored in both the stillserving US military population (Riddle 2007) and in the UK general population (Jenkins 1997).…”
Section: Common Mental Health Problems In Veteransmentioning
confidence: 63%
“…A clear view that emerged from the stakeholders and veterans interviewed was that the mental health needs of veterans were not being met by existing National Health Service (NHS) provisions at that time. A more recent cross-sectional study examining health service utilisation in those who have left the British armed forces (Iversen 2005b) has confirmed the anecdotal impression. It found that only 58% of those who reported mental health problems were currently seeking help from any professional, and only 28% had sought help from a non-governmental organisation.…”
Section: Improving the Mental Health Of Ex-service Personnel And Resementioning
confidence: 74%
See 1 more Smart Citation
“…Research suggests that treatment offered by these services is likely to benefit a significant number of veterans were they to access the help (Kitchiner, Roberts, Wilcox, & Bisson, 2012). However, evidence suggests that UK veterans often under use these services (Greenberg, 2014), with only around 50% of veterans seeking help for mental health problems (Iversen et al, 2005). In addition, research indicates that veterans may experience mental health difficulties for as long as 12 years after leaving the Armed Forces (AF) before they seek professional help (Murphy, 2016).…”
mentioning
confidence: 99%
“…It has been observed that ex-service personnel with untreated PTSD are at particular risk (Iversen et al, 2005) and that veterans who have been diagnosed with PTSD have poorer outcomes following treatment than non-military peers with PTSD (Watts, Schnurr, Mayo, Young-Xu, Weeks, & Friedman, 2013;Bradley, Greene, Russ, Dutra, & Weston, 2005).…”
mentioning
confidence: 99%